Microwave-induced thermal sterilization- A review on history, technical progress, advantages and challenges as compared to the conventional methods. (March 2020) - Soni, Aswathi; Smith, Jeremy; Thompson, Abby; Brightwell, Gale
Abstract: Microwave-assisted thermal sterilizsation (MATS) technology combines the energy from microwaves of long-wavelength (915 MHz) along with hot water immersion to sterilize food in polymeric packages. MATS is presumed to be a successful sterilization method to eliminate pathogens including bacterial spores, improve the shelf-life of food products while the nutritive qualities and flavours are not affected (within consumer acceptance). From the regulatory point of view, it is a thermal technology for pre-packaged commercial sterilization of homogeneous and nonhomogeneous foods as accepted by the Food and Drug Administration (FDA). Scope and approach: This review covers the technical progress, advantages and challenges associated with MATS technology with a comparison to conventional methods and its potential in the food industry. This comprehensive background study is worth considering while developing protocols and validation assays for MATS. Key findings: MATS is postulated to not only eliminate the edge-heating issues, but it also reduces the heat exposure time to minimize the effect on heat-sensitive components while achieving maximum microbial inactivation. MATS technology has promising potentials and has been expected to have comparable results if not better to retorting in sterilization while ensuring better sensory qualities and attribute that influence consumer acceptance. Hence, bridging the gaps with enhanced efforts in the field of food safety and sensory science would not only provide an upper hand to the technology but would also increase commercialization by meeting the market needs. Highlights: MATS can reduce the undesirable effects of heat on food during sterilization. MATS can increase nutrient retention and reduce the effect on sensory attributes. MATS provides shelf life comparable to retorting. Sterilization of heat sensitive products can be achieved.